The Protection of Personal Data in the NHS. - Scrivens, Ellie (Political Quarterly)
Discusses key issues concerning personal data protection in the National Health Service of Great Britain in 1985. Passage and key stipulations of the Data Protection Act in 1984; Eight principles of data protection covered by the legislation; Implications on the rights of patients and consumers.